2023
DOI: 10.1039/d2py00972b
|View full text |Cite
|
Sign up to set email alerts
|

A user-guide for polymer purification using dialysis

Abstract: Dialysis diffusion kinetics are performed via in-situ NMR spectroscopy for numerous different raw polymeric solutions to result in a general guideline for polymer purification using dialysis. In several approaches, a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Recent studies on polymer diffusion kinetics during dialysis have revealed crucial influence of chemical composition on polymer retention. , Given the inherent sequence heterogeneity of RHPs, it naturally leads to the question of whether certain RHP chains are removed during the purification process (Scheme ). Thus, we monitored the composition evolution of RHP1–4 at every stage of the preparation process (Figure a, synthesis details in Section S2).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies on polymer diffusion kinetics during dialysis have revealed crucial influence of chemical composition on polymer retention. , Given the inherent sequence heterogeneity of RHPs, it naturally leads to the question of whether certain RHP chains are removed during the purification process (Scheme ). Thus, we monitored the composition evolution of RHP1–4 at every stage of the preparation process (Figure a, synthesis details in Section S2).…”
Section: Resultsmentioning
confidence: 99%
“…39 This system is based on a benchtop NMR device, which already gained much interest in academic research. [40][41][42][43] By the use of ow cells, a continuous circulation of the reaction solution through the analytical capillary is possible. 44 Therefore, no sampling process is required and, thus, the spectroscopic technique does not affect the catalytic system.…”
Section: Cooperative Effectmentioning
confidence: 99%
“…the influence of polymers on the purification rate, [78] but also the fully automated synthesis of block copolymers with incomplete conversion during the reactions. [79] First, a polymer was produced using RAFT polymerization in the synthesis robot, purified, and then converted into the block copolymer in the synthesis robot.…”
Section: Purificationmentioning
confidence: 99%
“…As a result, the reaction mixture could be automatically transferred to the dialysis directly after the reaction and back again after the purification was completed. In addition, a corresponding approach could also be linked to monitoring using online NMR spectroscopy, which enabled the investigation of kinetics [ 77 ] and the influence of polymers on the purification rate, [ 78 ] but also the fully automated synthesis of block copolymers with incomplete conversion during the reactions. [ 79 ] First, a polymer was produced using RAFT polymerization in the synthesis robot, purified, and then converted into the block copolymer in the synthesis robot.…”
Section: Polymer Synthesismentioning
confidence: 99%